2019
DOI: 10.1021/acs.accounts.8b00489
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Rheological Properties of Liquid Metals To Shape Soft Electronic Conductors for Wearable Applications

Abstract: Emerging applications of the Internet of Things in healthcare, wellness, and gaming require continuous monitoring of the body and its environment, fueling the need for wearable devices able to maintain intimate, reliable, and unobtrusive contact with the human body. This translates in the necessity to develop soft and deformable electronics that match the body's mechanics and dynamics. In recent years, various strategies have been proposed to form stretchable circuits and more specifically elastic electrical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 70 publications
0
63
0
Order By: Relevance
“…Furthermore, a recent study showed that the hydrophobic polymer coating method stabilized LM NPs for more than 60 days. [219] When WFHE are intended to have hybrid functions on drug release, a multilayered film composed of the hydrophilic mesh containing therapeutic agents and hydrophobic encapsulation layers can function to release drugs. [245] Since the crack propagation is induced by strain due to the mechanical mismatch at the surface, water infiltration and drug release occurred subsequently.…”
Section: Water Repellencymentioning
confidence: 99%
“…Furthermore, a recent study showed that the hydrophobic polymer coating method stabilized LM NPs for more than 60 days. [219] When WFHE are intended to have hybrid functions on drug release, a multilayered film composed of the hydrophilic mesh containing therapeutic agents and hydrophobic encapsulation layers can function to release drugs. [245] Since the crack propagation is induced by strain due to the mechanical mismatch at the surface, water infiltration and drug release occurred subsequently.…”
Section: Water Repellencymentioning
confidence: 99%
“…Highly elastic and stretchable conductive materials are needed for the electrodes and interconnects. Examples include composite percolation networks of conductive particles and elastomers (Figure a), and inherently stretchable materials (Figure b) such as liquid eutectic metals or conducting polymers demonstrated to maintain a conductivity ≈100 S cm −1 under 800% tensile strain. Thin film metals have been made into highly conformal, stretchable conductors by geometry optimization using serpentine or cilia structures (Figure c)…”
Section: Sensor Materialsmentioning
confidence: 99%
“…This property has been leveraged to counterbalance surface tension and stabilize the material, enabling the formation of metastable shapes . On the other hand, the amphoteric oxide skin hinders further processing as it can be removed only by reaction with acid or alkaline solutions, requiring the development of special patterning techniques adapted to the complex rheology of gallium . Processing solutions reported in the literature require either pressurizing the liquid metal and rupturing the oxide skin to enable shaping before the oxide skin regrowth, or removing the oxide skin in a reducing environment and allowing wetting of the liquid metal on a galliophilic pattern .…”
mentioning
confidence: 99%